Action research a handbook for practitioners - Stringer, Ernest T. (Sage, 1996)
It provides a series of tools to assist the novice practitioner researcher in moving more comfortably through the research process. After defining and setting community-based action research into the context of qualitative research methodology, the book describes an uncannily simple but effective model for approaching action research.